State as terrorist : kāwan[a]tanga te kaiwhakatuma : Parihaka 1881, Maungapohatu 1916, Ruatoki 2007 : a thesis submitted in partial fulfillment of the requirements for the degree of Master of Arts in Māori Studies at Massey University - Pearless, Harawira Craig (Massey University, 2009)
This thesis explores New Zealand Policing practice during the invasions, expeditions and raids at Parihaka 1881, Maungapohatu 1916 and Ruatoki 2007. An analysis is provided of the consequences and dynamics of governance by force and State's action against Maori in these three cases. Policing practices at Parihaka 1881, Maungapohatu 1916 and Ruatoki 2007 are described and a critique of the trends and politics are provided to support the thesis that state terror was orchestrated by the respective governments of the day and delivered coercively against Maori by the New Zealand Police to procure land, suppress Maori leadership and disavow Maori assertions of sovereignty. In this context it is argued that these actions can be considered what Stohl1 refers to as acts of state terror which over time have oppressed, repressed, and terrorized Maori. It is argued that the state and the state's enforcers have used acts of state terror against Maori to quash legitimate assertions of Maori self determination after labeling Maori actions as nationalist dissidence.
Keywords: State-sponsored terrorism; New Zealand; History; Insurgency; Maori; Government relations; Parihaka Pa; Maungapohatu; Ruatoki; Kōrero nehe; Tōrangapū; Politics and government